Devaluation of values or a creative need to transcend into the depth? - Kanišauskas, Saulius (Creativity Studies, 2018)
The recent decades have witnessed the increased society’s attention to values based on welfare state and the economics of happiness, and this however becomes worrying. The term of “value” has started to be employed inarticulately and irresponsibly in public and even creative discourses. Thus, the question arises whether we face the process of devaluation of values? The paper reflects on contemporary tendencies of research in axiology and maintains that the increased focus on values appears not due to the lack of satisfying material needs but because of the unconscious creative need to transcend into the depth, that is because of ontological longing for something absolutely genuine.Article in English.Vertybių devalvacija ar kūrybinis poreikis transcendentuoti į gelmę?SantraukaPastaraisiais dešimtmečiais su gerovės valstybe ir laimės ekonomika siejamas smarkiai išaugęs visuomenės dėmesys vertybėms ima kelti nerimą. Terminas vertybė viešuosiuose ir net kūrybiniuose diskursuose pradėtas vartoti neartikuliuotai, neatsakingai. Todėl kyla klausimas – ar neprasidėjo vertybių devalvacijos procesas? Straipsnyje apžvelgiamos šiuolaikinių vertybinių tyrimų tendencijos ir parodoma, kad dėmesys vertybėms kyla ne tik dėl vis dar esančios materialių poreikių patenkinimo stokos, bet ir dėl neįsisąmoninto kūrybinio poreikio transcendentuoti į gylį, ontologinio ilgesio to, kas iš tiesų yra tikra.Reikšminiai žodžiai: kūrybiškumas, laimės ekonomika, stoka, dvasingumas, vertybės, dorybės.